Standort Düsseldorf. - Kunsthalle, Düsseldorf (Düsseldorf : Kunsthalle Düsseldorf, 1983)
Bachhuber, Liz ; Boehle, Hilmar ; Ecker, Bogomir ; Genzken, Isa ; Gerdes, Ludger ; Gieseler, Manfred ; Huber, Thomas ; Irmer, Michael ; Kasseböhmer, Axel ; Klingelhöller, Harald ; Knöller, Paco ; Lohmann, Julia ; Mucha, Reinhard ; etc.
Standort Düsseldorf, Kunsthalle Düsseldorf, 8. - 23. Oktober 1983
boek